2005
DOI: 10.1177/095632020501600504
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Activity of 1H-benzotriazole and 1H-benzimidazole Analogues — Inhibitors of the NTPase/Helicase of HCV and of Some Related Flaviviridae

Abstract: To improve anti-helical activity of analogues of 1H-benzotriazole and 1H-benzimidazole their N-alkyl derivatives were synthesized and tested for antihelicase activity against enzymes of selected Flaviviridae including hepatitis C virus (HCV), West Nile virus (WNV), Dengue virus (DENV) and Japanese encephalitis virus (JEV). 1- and 2-alkyl derivatives of 4,5,6,7-tetrabromo-1H-benzotriazole were obtained by direct alkylation of 4,5,6,7-tetrabromo-1H-benzotriazole with the use of respective alkyl halides in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 29 publications
0
29
0
1
Order By: Relevance
“…Targeted reduction or point mutants of NTPase inhibit Toxoplasma gondii proliferation (31) and viral DNA replication (20). Small molecules designed to inhibit NTPase function may be promising antiviral drugs (3,8,34,38).…”
Section: Discussionmentioning
confidence: 99%
“…Targeted reduction or point mutants of NTPase inhibit Toxoplasma gondii proliferation (31) and viral DNA replication (20). Small molecules designed to inhibit NTPase function may be promising antiviral drugs (3,8,34,38).…”
Section: Discussionmentioning
confidence: 99%
“…The hydrazones 8-12 were synthesized by condensation of carbohydrazide 7 with aromatic aldehydes or ketones-acetone and ethylmethylketone. Analysis of 1 H NMR spectra of 1-aryl-3-arylidenehydrazinocarbonyl-5-oxopyrrolidines [8][9][10][11][12] showed that a mixture of E/Z rotamers exists in DMSO-d 6 solutions in which Z isomer predominates due to a hindered rotation around the CO-NH bond [20,21].…”
Section: Resultsmentioning
confidence: 99%
“…Benzimidazole derivatives are distinguished for antimicrobial [1][2][3][4], antifungal [5][6][7], antiviral [8], anthelmintic [9,10], antihypertensive [11], antihistaminic [12], analgesic [13], and anti-HIV [14] actions. Also, some of benzimidazoles are used in coordination chemistry [15,16], in optoelectronics [17], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of substituted benzimidazole derivatives is of considerable importance, because most of these compounds have a promising biological activity [1][2][3][4][5][6][7][8][9][10]. Also, the compounds whose molecules possess an azole ring, such as pyrrole [11][12][13], 1,3,4-oxadiazole [14][15][16][17][18][19] and 1,2,4-triazole [19][20][21][22][23], are often characterized as good antimicrobial agents.…”
Section: Introductionmentioning
confidence: 99%